ANALISIS KEPUTUSAN MASYARAKAT BERINVESTASI LOGAM MULIA PADA PT PEGADAIAN DI KOTA TIMIKA - Sumardiono; Windy Vidyawati, Siske Tontong (CV. ADIBA AISHA AMIRA, 2023)
This research aims to determine the determining factors in people's decisions to invest in precious metals at PT Pegadaian. The research method used is descriptive research method. In this research, the data collection techniques used were observation and questionnaires. To find out the determining factors in people's decisions to invest in precious metals at PT Pegadaian in Timika City, the data analysis instrument used is confirmatory factor analysis (CFA). The results of this research show that of the four factors confirmed as determining factors in people's decisions to invest in precious metals at PT Pegadaian in the city of Timika and the dominant factor is psychological factors